Small nations and colonial peripheries in World War I - Barry, Gearóid 1977-; Dal Lago, Enrico 1966-; Healy, Róisín 1969- (History of warfare, 2016)
"This edited volume examines the experience of World War I of small nations, defined here in terms of their relative weakness vis-à-vis the major actors in European diplomacy, and colonial peripheries, encompassing areas that were subject to colonial rule by European empires and thus located far from the heartland of these empires. The chapters address subject nations within Europe, such as Ireland and Poland; neutral states, such as Sweden and Spain; and overseas colonies like Tunisia, Algeria and German East Africa. By combining analyses of both European and extra-European experiences of war, this collection of essays provides a unique comparative perspective on World War I and points the way towards an integrated history of small nations and colonial peripheries. Contributors are Steven Balbirnie, Gearóid Barry, Jens Boysen, Ingrid Brühwiler, William Buck, AUde Chanson, Enrico Dal Lago, Matias Gardin, Richard Gow, Florian Grafl, Dónal Hassett, Guido Hausmann, Róisín Healy, Conor Morrissey, Michael Neiberg, David Noack, Chris Rominger, Danielle Ross and Christine Strotmann"...Provided by publisher